Outcome Knowledge and False Belief - Ghrear, Siba E.; Birch, Susan A. J.; Bernstein, Daniel M. (Frontiers in Psychology, 2016)
Virtually every social interaction involves reasoning about the perspectives of others, or ‘theory of mind’. Previous research suggests that it is difficult to ignore our current knowledge when reasoning about a more naïve perspective (i.e., the curse of knowledge). In this Mini Review, we discuss the implications of the curse of knowledge for certain aspects of theory of mind. Particularly, we examine how the curse of knowledge influences key measurements of false belief reasoning. In closing, we touch on the need to develop new measurement tools to discern the mechanisms involved in the curse of knowledge and false belief reasoning, and how they develop across the lifespan.